A system for evaluating the impact of noise pollution on the population's health - Bressane, Adriano [UNESP]; Mochizuki, Patricia Satie; Caram, Rosana Maria; Frutuoso Roveda, Jose Arnaldo [UNESP] (Cadernos Saude Publica, 2016)
The aim of this study was to develop a support system for the evaluation of noise pollution, applied to the central urban area of Rio Claro, Sao Paulo State, Brazil. Data were obtained from noise measurements and interviews with the population, generating the following indicators: equivalent sound level (L-eq), traffic noise index (L-TNI), and a participatory diagnosis (D-p), integrated through a fuzzy inference system (FIS). The proposed system allowed classifying the measurement points according to the degree of impact of noise pollution on the population's health (I-PS) in the study area. Impact was considered significant in 31.4% of the measurement points and very significant in 62.9%. The FIS can be adjusted to local conditions, allowing generalization and thus also supporting noise pollution evaluation and respective environmental noise management in other geographic areas.
Keywords: Fuzzy Logic; Sound Contamination; Noise Effects